Adopsi Financial Technology oleh Bank Syariah Indonesia (BSI) dalam Meningkatkan Inklusi Keuangan Syariah di Era Digital - Masyita Auliyah; Andriani Samsuri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of financial technology (fintech) has brought about a significant transformation in the global financial industry, including in Indonesia. Bank Syariah Indonesia (BSI) as one of the largest Islamic banks in Indonesia, has adopted fintech to increase Islamic financial inclusion in the digital era. This study aims to analyze how the adoption of fintech by BSI can expand access to Islamic financial services, especially for people in remote areas and MSMEs. The research method used is qualitative descriptive by collecting secondary data from scientific journals, books, and so on. The results of the study show that digital innovations such as BSI Mobile, BSI QRIS, and collaboration with fintech platforms have succeeded in increasing the accessibility of Islamic financial services. BSI's digital transactions reached 97.94%, with ZISWAF transactions through BSI Mobile growing 31% in September 2024. The adoption of fintech by BSI not only increases operational efficiency, but also strengthens Islamic financial literacy and empowers MSMEs and rural communities. Thus, BSI has created an inclusive, accessible, and Islamic financial ecosystem.